2022
DOI: 10.1002/brb3.2675
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitive C‐reactive protein‐albumin ratio is associated with stroke‐associated pneumonia and early clinical outcomes in patients with acute ischemic stroke

Abstract: Objectives:We aimed to explore the association between the baseline hypersensitive C-reactive protein-albumin ratio (CAR) and stroke-associated pneumonia (SAP) during hospitalization and the short-term prognosis in patients with acute ischemic stroke (AIS). Methods:We enrolled 766 patients with AIS and collected their admission baseline characteristics, including their National Institutes of Health Stroke Scale score, CAR, age, atrial fibrillation, dysphagia, sex, stroke severity (A 2 DS 2 ) score, and other i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Studies have shown that stroke-related infections, especially pneumonia, are independently associated with poor functional prognosis after stroke. Our study also observed that subjects with SAP had worse functional outcomes at 3-month followup, consistent with previous studies (38)(39)(40). Two phase-II studies on prophylactic antibiotic therapy showed benefits on temperature, the incidence of infection, and even functional outcomes (41,42).…”
Section: Discussionsupporting
confidence: 93%
“…Studies have shown that stroke-related infections, especially pneumonia, are independently associated with poor functional prognosis after stroke. Our study also observed that subjects with SAP had worse functional outcomes at 3-month followup, consistent with previous studies (38)(39)(40). Two phase-II studies on prophylactic antibiotic therapy showed benefits on temperature, the incidence of infection, and even functional outcomes (41,42).…”
Section: Discussionsupporting
confidence: 93%
“…The diagnosis of SAP was based on the modified Centers for Disease Control and Prevention criteria of hospital-acquired pneumonia by two trained clinicians, according to clinical and laboratory parameters of acute lower respiratory tract infection, and was confirmed by chest X-ray or CT [ 6 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…In China, ischemic stroke serves as one of the main reasons for mortality and long-term disability in elderly people [ 1 , 2 , 3 ]. However, approximately 7–38% of acute ischemic stroke (AIS) patients suffer from stroke-associated pneumonia (SAP), which may lead to unfavorable prognosis and disability [ 4 , 5 , 6 , 7 , 8 , 9 ]. Hence, it is valuable and meaningful to explore novel biomarkers for SAP prediction in AIS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, biomarkers implicated in immune alterations and systemic inflammatory responses may play a role in SAP development. Studies have linked parameters such as white blood cell count, neutrophil count, lymphocyte count, as well as inflammatory biomarkers like the monocyte-to-lymphocyte ratio and the C-reactive protein albumin ratio, to adverse outcomes in SAP episodes and stroke 4 , 5 . Malnutrition is common among patients with ICH and is linked to higher risks of all-cause mortality and unfavorable functional outcomes 6 .…”
Section: Introductionmentioning
confidence: 99%